Relating organizational knowledge with ISO 9001: 2015: An empirical approach - Matos, F. (2022)
In a business market environment highly marked by competition, standardisation has proven distinctive in answering continuous challenges. Thus, organisations have been investing in obtaining ISO certifications, being "ISO 9001 – Quality Management System" among the most popular. The present empirical study aims to discover what is, in the opinion of managers expressed by their answers to the questionnaire, the relationship between the implementation of Knowledge Management practices, the Quality System and Organizational Performance while verifying if the introduction of Knowledge Management principles in the Standard ISO 9001 has affected the company's overall organisational performance. The proposed analysis methodology is supported by applying a questionnaire to 36 Portuguese Small and Medium Enterprises sample. The investigation results allowed us to infer that, in the managers' opinion expressed by the answer to the questionnaire, Knowledge Management acts as a mediator between the Quality System and performance while not directly influencing organisational performance. Within the companies studied, holders of the certification ISO 9001, through the application of Knowledge Management practices, show improvements in the management of the Quality System, with a consequent increase in organisational performance.